(untitled) (Nigerian Journal of Technology, 2018)
Zungur watershed located in the southern region of Bauchi State has no record of existing flood plain mapping. This research integrated HEC-RAS with GIS to estimate the flood zone of Zungur Watershed. HEC-GeoRAS, an ArcView GIS extension HEC-RAS, was used to delineate the areas prone to flooding at different discharges of 2 to 100 years return periods. Area inundated by 2, 5, 10, 25, 50 and 100-year floods were 186.71, 189.15, 193.59, 197.63, 200.09 and 205.32 km2 respectively with maximum inundation depths ranging from 5.37 m to 7.37 m for 2 to 100 years. Flood inundation mapping showed that Zungur, Dass, Bagel, Sabongida, Mun, Birim, Talagutta and Gwani Settlements are likely to be affected by 100-year flood and agricultural land is the most affected landuse. The result of this study showed that hydraulic simulation and GIS could be effective for floodplain mapping and management. http://dx.doi.org/10.4314/njt.v37i4.41